NS1 Antigen and Laboratory Diagnosis of Dengue: A Narrative Review (Green Life Medical College Journal, 2026)
Dengue non-structural protein 1 (NS1) is a multifunctional viral antigen that acts as a potent immunomodulator of vascular and immune pathology in dengue. It circulates at high concentrations during acute infection. NS1 promotes endothelial dysfunction through multiple complementary mechanisms, including the engagement of pattern-recognition receptors (notably TLR4), which triggers the release of proinflammatory cytokines and leads to prolonged vascular leakage. Additionally, impaired coagulation contributes to hemorrhagic manifestations. On the diagnostic front, secreted NS1 is detectable during the early stages of infection, often concurrently with viremia and before antibody seroconversion, and has been successfully utilized in capture ELISA and rapid antigen tests. This narrative review focuses on the current role of NS1 in dengue pathogenesis, as well as on accurate and timely diagnosis of dengue, which is essential for early clinical management and preventing severe disease outcomes.Journal of Green Life Med. Col. 2026; 11(1): 23- 29